How ESG Disclosure Shapes Financial Resilience and Market Value of Indonesian Banks? - Sulaiman Sulaiman; Riana Mayasari; Indra Satriawan; Nurul Aulia Rahma; Rachmat Syawal; Rami Pebrian; R.A.Rahma Wahyuni (Politeknik Ganesha Medan, 2026)
The purpose of this study is to investigate the impact of ESG Disclosure on business financial performance, as measured by Return on Assets (ROA), Price to Book Value (PBV), and Return on Equity (ROE). The study’s population comprises all banking companies that were listed on the Indonesia Stock Exchange (IDX) during the 2021–2022 period. The sample was selected using a purposive sampling technique based on the criteria of Sustainability Report availability and complete financial data, yielding a total of 92 panel data observations. The research method is quantitative, utilizing Pearson correlation and simple regression analysis. The results show that ESG Disclosure has a beneficial and statistically significant impact on ROE (p = 0. 0164), but not on ROA (p = 0.1161) or PBV (p = 0. 3187). These findings indicate that the financial impact of ESG disclosure is selective, where the benefits are more evident in shareholder-oriented performance rather than in asset efficiency or market valuation. The results highlight the importance of ESG transparency for enhancing investor confidence and sustainable financial growth in the Indonesian banking sector. These findings provide valuable insights for regulators and policymakers to strengthen ESG reporting standards and for investors to integrate sustainability information into financial decision-making.